The Effect of Some Instruments for Prothrombin Time Testing on the International Sensitivity Index (ISI) of Two Rabbit Tissue Thromboplastin Reagents - Poggio, Marina; Besselaar, Antonius M H P van den; Velde, Edo A van der; Bertina, Rogier M (Thrombosis and Haemostasis, 1989)
Two commercial rabbit tissue thromboplastins were calibrated against the International Reference Preparation for rabbit thromboplastin (coded RBT/79) by one laboratory using the manual technique, a semi-automatic electro-mechanical coagulometer and three different automatic photo-optical instruments. The calibration of the two reagents was performed in three and two different exercises, respectively, and showed good reproducibility of the procedure. The purpose of calibration is providing a formula for the assessment of the International Normalized Ratio (INR) for patients receiving oral anticoagulants. The World Health Organization (WHO) model for thromboplastin calibration leads to the equation INR = RISI, in which R is the prothrombin time ratio and ISI the International Sensitivity Index of the calibrated thromboplastin/instrument system. This equation was adequate for one reagent, but not for the other when it was used in combination with the four instruments. At therapeutic intensities of anticoagulation, the deviation from the WHO-model observed for the second reagent was clinically insignificant. The WHO model was fully adequate when the second reagent was used with the manual technique. For both thromboplastins, there were statistically significant differences in ISI between the four instruments. The largest difference-amounting to approximately 10%-was observed between two photo-optical instruments. The order of instruments with increasing ISI was the same for the two reagents. It is recommended that thromboplastin manufacturers specify the instruments used for calibration of their reagent.
Keywords: Oral anticoagulant control; Prothrombin time; Thromboplastin calibration; International Sensitivity Index; Instrument effect